Pendekatan Desain Holistik: High-Tech, Honai, dan Nilai Islam pada Desain Merauke Aquatic Center - Khairina, Ade; Marwati, Marwati; Amin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2025)
A holistic design approach to water sports facilities is offered through a combination of High-Tech architecture, traditional Honu Papua forms, and the integration of Islamic values. Honai, with its circular geometry and conical roof, was adapted as inspiration for mass composition to form a strong, contextual visual identity and has the potential to become a regional landmark. Meanwhile, the High-Tech principle is realized through an emphasis on exposed steel structures, the use of light and technological materials, the application of wide spans, and technological expressions in facade elements and building details, to support safe, efficient, and environmentally friendly construction. Islamic values are integrated by interpreting water as an element of benefit and by encouraging the responsible use of technology, so that the design is not only functional and aesthetic but also ethical and spiritual. This study uses a descriptive method through literature review and design concept analysis, which is then applied to the design of a representative Aquatic Sports Center. The exploration results show that the combination of the Honai form, High-Tech principles, and Islamic values allows the creation of an Aquatic Center that is modern, has local character, and meets functional standards for the development of contextual, sustainable sports facilities.